Makna Zikir Perspektif Mufassir Modern di Indonesia - Achyar Zein (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2015)
This article concerns with the interpretation of the Quranic verses on dhikr (rememberance) in their various forms and contexts. It seeks to explore a great variety of exegesis (tafs?r) literature written by Indonesian exegetes such as Mahmud Yunus, Hasby ash-Shiddieqy, Hamka and M. Quraish Shihab. Using the method of comparative exegesis (tafs?r muq?rin), this article aims to reveal how these Indonesian exegetes (mufassir?n) interprete the verses of dhikr. The understanding of Indonesian exegetes towards dhikr varies greatly, causing difference in interpreting the verses. However, the exegetes share the understanding that dhikr is an activity of remembering God, spelling out the names of God orally, and actualizing God?s teachings physically. Despite the fact that those exegetes shares commonalities in interpreting the verses of dhikr, they are also different to one another especially in dealing with their perspectives such as historical contexts and language aspects.